Group causation theories and deterrence of tortious acts - Urs Schweizer (European Journal of Law and Economics, 2025)
This paper examines a model with multiple actors, each of whom faces a binary action choice. The action choice imposes harm on a victim that depends on the number of actors who enter or, alternatively, who deviate from a due care standard. The paper examines incentive and welfare effects from per-capita liability under simultaneous as well as sequential action choice. The challenge is to cope with due care standards that, for whatever reasons, need not be efficient. As it turns out, welfare is enhanced in any equilibrium as compared to the situation where none of the actors enter or, alternatively, where all of them meet the due care standard. The range of parameter values, however, where a welfare maximizing outcome in equilibrium is induced by per-capita liability turns out to be rather limited. As an alternative rule, efficient per-capita liability is proposed that would lead to an efficient outcome quite generally for simultaneous as well as sequential action choice.
Keywords: K13; 340; Group causation; Per-capita liability; Efficient deterrence; Inefficient due care standards; Sequential action choice